2020
DOI: 10.1073/pnas.2003621117
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation-dependent opsonophagocytic activity of staphylococcal protein A antibodies

Abstract: Antibodies may bind to bacterial pathogens or their toxins to control infections, and their effector activity is mediated through the recruitment of complement component C1q or the engagement with Fcγ receptors (FcγRs). For bacterial pathogens that rely on a single toxin to cause disease, immunity correlates with toxin neutralization. Most other bacterial pathogens, including Staphylococcus aureus, secrete numerous toxins and evolved multiple mechanisms to escape opsonization and complement killing. Several va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Additionally, passive neutralization of SpA encourages production of effective anti-staphylococcal antibodies that promote bacterial decolonization from nasal and gastrointestinal mucosa of mice ( Chen et al, 2019 ). Furthermore, humanized anti-SpA KKAA antibodies promote bacterial clearance upon binding SpA through the induction of the complement cascade, and effective complement activation is dependent upon the glycosylation of SpA-binding mAbs ( Chen et al, 2020 ). SpA KKAA has been proposed as part of a four-antigen S. aureus vaccine that demonstrates improved survival in systemic S. aureus infection in mice ( Kim et al, 2011 ; Rauch et al, 2014 ).…”
Section: Antivirulence Strategiesmentioning
confidence: 99%
“…Additionally, passive neutralization of SpA encourages production of effective anti-staphylococcal antibodies that promote bacterial decolonization from nasal and gastrointestinal mucosa of mice ( Chen et al, 2019 ). Furthermore, humanized anti-SpA KKAA antibodies promote bacterial clearance upon binding SpA through the induction of the complement cascade, and effective complement activation is dependent upon the glycosylation of SpA-binding mAbs ( Chen et al, 2020 ). SpA KKAA has been proposed as part of a four-antigen S. aureus vaccine that demonstrates improved survival in systemic S. aureus infection in mice ( Kim et al, 2011 ; Rauch et al, 2014 ).…”
Section: Antivirulence Strategiesmentioning
confidence: 99%
“…It has been shown that human antibody N-glycosylation (IgG glycan at N297) and the structure of the N-glycan are important for antibody functionality ( Krapp et al, 2003 ; Jefferis, 2009 ). For example, changes in IgG glycosylation play a role in autoimmune disease and cancer in humans and impact viral and bacterial colonization ( Chen et al, 2020 ; Irvine and Alter, 2020 ). But little is known about IgY glycosylation and its contribution to antibody functionality in chickens.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse mAb 3F6 binds to each of the five immunoglobulin-binding domains (IgBDs) of SpA, blocks IgG binding to SpA and protects against bloodstream infection when administered to mice [ 85 , 86 , 87 ]. A human version of this antibody (3F6-hIgG1) improves the outcome of MRSA bloodstream infections in animal models [ 87 , 88 ] and its Fc glycosylation enhances C1q binding and the recruitment and killing of staphylococci by phagocytosis and favors protection against infection [ 101 ]. Moreover, Varshney et al isolated and studied a human mAb, named 514G3, belonging to the subclass IgG3, a condition that does not allow binding via the Fc region to SpA.…”
Section: Mabs Targeting Virulence Factors and Their Possible Therapeutic Use To Combat Staphylococcal Infectionsmentioning
confidence: 99%